2011
DOI: 10.1152/ajpendo.00261.2011
|View full text |Cite
|
Sign up to set email alerts
|

Increased maternal fat consumption during pregnancy alters body composition in neonatal mice

Abstract: Krasnow SM, Nguyen MT, Marks DL. Increased maternal fat consumption during pregnancy alters body composition in neonatal mice. Am J Physiol Endocrinol Metab 301: E1243-E1253, 2011. First published September 6, 2011 doi:10.1152/ajpendo.00261.2011Maternal overnutrition prior to and during gestation causes pronounced metabolic dysfunction in the adult offspring. However, less is known about metabolic adaptations in the offspring that occur independently of postnatal growth and nutrition. Therefore, we evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 76 publications
(85 reference statements)
3
40
0
Order By: Relevance
“…This can be associated with increased body length (8); however, increases in lean mass are less obvious (24). The HFS-induced pup growth and development may be dampened by intense behavioral and metabolic activities (37).…”
Section: Discussionmentioning
confidence: 99%
“…This can be associated with increased body length (8); however, increases in lean mass are less obvious (24). The HFS-induced pup growth and development may be dampened by intense behavioral and metabolic activities (37).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has emerged from studies on the independent effects of maternal high-fat feeding that support the hypothesis that increased circulating lipids, as opposed to maternal obesity per se, are the mediator of fetal programming (36,43,65). Importantly, gestational exposure to high-fat diets has been associated with epigenetic changes (histone acetylation and methylation) in adipokine genes (43) and genes regulating glucose metabolism (65) in offspring tissues.…”
Section: E11mentioning
confidence: 99%
“…Models of maternal overnutrition and obesity rely on feeding the dams a high-fat (HF) or highenergy/cafeteria (fat and sugar) diet before (preconceptional period) and/or during gestation and/or lactation. In rodents, studies on maternal overfeeding have reported variable effects on birth weight, ranging from low to normal to high values (51,67,80). The discrepancy between these studies may be related to the complex interaction between maternal diet composition and genotypic susceptibility of individual rodent strains.…”
Section: Malnourished Offspring Display Altered Adipogenesis and Fat mentioning
confidence: 99%